Deep Learning based Visual Quality Control - Toğa, Gülhan; Karaman, Berkay; Kömü, Şemsi Nur; Cingöz, Mehmet; Aksoy, Kadir Can (Fırat University, 2026)
In this study, a deep learning–based visual quality control system was developed to detect enamel coating defects on stove burner caps obtained from the production process. For image classification, transfer learning–based Convolutional Neural Network architectures, namely MobileNetV2 and DenseNet121, were employed. Since the number of raw images was limited, data augmentation and normalization techniques were applied to enhance the model’s generalization capability. To mitigate class imbalance, the dataset was divided into training, validation, and test sets using stratified sampling, and class weights were incorporated during model training. The models’ performances were evaluated using metrics such as accuracy, loss, confusion matrix, and ROC curves. The results demonstrated that the developed models achieved over 91% classification accuracy with MobileNetV2 and over 90% with DenseNet121, effectively distinguishing defective products with high precision and sensitivity. These findings indicate that deep learning and image processing–based approaches provide an efficient, consistent, and automated solution for industrial quality control processes, reducing human error and inspection costs while offering strong potential for integration into Industry 4.0–compliant systems.

Bu çalışmada, üretim sürecinde elde edilen ocak bek kapağı görselleri üzerinde emaye kaplama kusurlarının tespiti amacıyla derin öğrenme tabanlı bir görsel kalite kontrol sistemi geliştirilmiştir. Görsel verilerin sınıflandırılmasında Evrişimsel Sinir Ağı mimarilerinden MobileNetV2 ve DenseNet121 transfer öğrenme yöntemleri kullanılmıştır. Ham görüntü sayısının sınırlı olması nedeniyle, modellerin genelleme yeteneğini artırmak amacıyla veri artırma ve normalizasyon işlemleri uygulanmıştır. Sınıf dengesizliğini azaltmak adına veri kümesi, katmanlı örnekleme ile eğitim, test ve doğrulama kümelerine ayrılmış, sınıf ağırlıkları dikkate alınarak modellerin eğitimi gerçekleştirilmiştir. Modellerin performansı doğruluk, kayıp oranı, karışıklık matrisi, ROC eğrileri ve AUC değerleri gibi metrikler ile değerlendirilmiştir. Sonuçlar, MobileNetV2 mimarisinde %91’in üzerinde, DenseNet121 mimarisinde ise %90’ın üzerinde sınıflandırma doğruluğu ile geliştirilen modellerin kusurlu ürünleri yüksek hassasiyet ve duyarlılıkla ayırt edebildiğini ortaya koymuştur. Bu bulgular, derin öğrenme ve görüntü işleme tabanlı yaklaşımların endüstriyel kalite kontrol süreçlerinde etkin, tutarlı ve otomatik bir çözüm sunduğunu; insan hatalarını ve denetim maliyetlerini azaltarak Endüstri 4.0 uyumlu sistemlere entegrasyon için güçlü bir potansiyel taşıdığını göstermektedir.
Derin Öğrenme Tabanlı Görsel Kalite Kontrol
Keywords: Manufacturing Safety and Quality; İmalat Güvenliği ve Kalite